MiRNA‐1 and miRNA‐133a are involved in early commitment of pluripotent stem cells and demonstrate antagonistic roles in the regulation of cardiac differentiation. (10th December 2014) - Izarra, Alberto; Moscoso, Isabel; Cañón, Susana; Carreiro, Candelas; Fondevila, Dolors; Martín‐Caballero, Juan; Blanca, Vanessa; Valiente, Iñigo; Díez‐Juan, Antonio; Bernad, Antonio
Abstract: miRNA‐1 (miR‐1) and miRNA‐133a (miR‐133a) are muscle‐specific miRNAs that play an important role in heart development and physiopathology. Although both miRNAs have been broadly studied during cardiogenesis, the mechanisms by which miR‐1 and miR‐133a could influence linage commitment in pluripotent stem cells remain poorly characterized. In this study we analysed the regulation of miR‐1 and miR‐133a expression during pluripotent stem cell differentiation [P19.CL6 cells; embryonic stem cells (ESCs) and induced pluripotent stem cells (iPSCs)] and investigated their role in DMSO and embryoid body (EB)‐mediated mesodermal and cardiac differentiation by gain‐ and loss‐of‐function studies, as well as in vivo, by the induction of teratomas. Gene expression analysis revealed that miR‐1 and miR‐133a are upregulated during cardiac differentiation of P19.CL6 cells, and also during ESC and iPSC EB differentiation. Forced overexpression of both miRNAs promoted mesodermal commitment and a concomitant decrease in the expression of neural differentiation markers. Moreover, overexpression of miR‐1 enhanced the cardiac differentiation of P19.CL6, while miR‐133a reduced it with respect to control cells. Teratoma formation experiments with P19.CL6 cells confirmed the influence of miR‐1 and miR‐133a during in vivo differentiation. Finally, inhibition of both miRNAs during P19.CL6 cardiac differentiation had opposite results to their overexpression. In conclusion, gene regulation involving miR‐1 and miR‐133a controls the mesodermal and cardiac fate of pluripotent stem cells. Copyright © 2014 John Wiley & Sons, Ltd.